越南学生使用汉语近义词的偏误分析 - Hang Thi Thu Nguyen (Journal International Lingua Mandarin (JILIN), 2021)
This paper collects and analyzes the errors made by Vietnamese students in the Chinese Chinese Faculty of the University of Social Science and Humanities, Vietnam National University HCMC in the process of using synonyms in Chinese, understands the situation and types of errors, find out the causes of errors, so as to provide some measures for learners to correct their errors.